Time to breast cancer recurrence and associated predictors in Public Hospitals of Addis Ababa, Central Ethiopia: a retrospective Cohort Study - Yadessa Chala; Tesfaye Techane; Bonsisa Bekele; Tesfaye Girma; Warati Fekede; Chalchisa Abdeta; Kibiru Mardasa; Tolera Abdeta; Bedada Teshome; Gashaye Atinkut; Abdinasir Wako; Mohammed Adem; et al. (Journal of Cancer Research and Clinical Oncology)
Abstract Background Breast cancer recurrence is a significant concern when the disease returns following surgery. The time to recurrence and factors affecting it are not well studied in low-income countries. This study aimed to assess the time to recurrence and predictors of breast cancer among women treated in public hospitals of Addis Ababa, Ethiopia. Methods Retrospective cohort study was conducted from April 30 to May 30, 2024, among randomly selected 322 recorded cases. The study covered from September 11, 2018, to September 12, 2023. Data were collected by the Kobo toolbox and analyzed by Stata Version 15. The Cox proportional hazard model was used to identify predictor variables, with assumptions checked using the Schoenfeld residual/global test (0.79). Multi-collinearity was checked using the variance inflation factor (3.72). Variables with a P-value < 0.25 in bivariable analysis were entered into the final multivariable analysis. Variables with a P-value < 0.05 at 95% confidence level were considered independent predictors of recurrence. Result The recurrence-free survival (RFS) status at the median follow-up time was 87.5%. The incidence rate of breast cancer recurrence was 6.8 per 100 women years (95%CI = 5.34–8.13) follow-up. The 75%RFS time was 44 months (95CI% = 40–48). The proportion of RFS survival at 24, 36, 48, and 60 months was 91.93%, 83.3%, and 67.7%, 61% respectively. Women aged 40 & below (AHR = 3.32; 95%CI 1.80–5.88), Overweight (AHR = 1.95, 95%CI 1.06 -3.59), surgical margin positive (AHR = 2.1; 95%CI 1.20–4.02), axillary node-positive (AHR = 1.98; 95%CI 1.08–3.61) and comorbidity (AHR = 4.45, 95%CI 2.39–8.30) were independent predictors for increased hazard of recurrence. Conclusion This study confirms a substantial incidence of breast cancer recurrence, with identifiable predictors including comorbidity, age, overweight, positive axillary node status, lymph node involvement, and deep surgical margin. Targeted interventions aimed at improving patient understanding of recurrence risk, promoting adherence to treatment protocols, and fostering healthy lifestyle modifications are crucial for reducing recurrence rates.